The Role of Artificial Intelligence on Digital Marketing: A Literature Study - Sebrina, A. Saddiyah; Haeruddin, M. Ilham Wardhana; Amin, Andi Mustika; Ramli, Anwar; Anwar, Anwar; Mustafa, Muh. Yushar (Entrepreneurship, Management, and Business Research Journal, 2025)
Artificial Intelligence, or AI, has emerged as a disruptive force in the digital marketing landscape, fundamentally altering how organizations interact with consumers. This literature study systematically evaluates the role of AI in digital marketing by synthesizing research published between 2020 and 2026. The study focuses on the transition from traditional rule-based systems to autonomous, generative, and predictive models. Key findings indicate that AI enhances marketing performance through hyper-personalization, automated content generation, and sophisticated predictive analytics. However, the study also identifies significant gaps in ethical frameworks and data privacy governance. The paper concludes by proposing a symbiotic model where AI-driven efficiency is balanced by human-centric strategic oversight.